Ответ(ы) на вопрос:
Исходное не пишу. Перейдём к решению сразу:
[latex] \frac{1}{4} (1 - 3x) + \frac{1}{2} (x^2 - 1) = 2 [/latex]
[latex] \frac{x^2}{2} - \frac{3x}{4} - \frac{1}{4} = 2 [/latex]
[latex]x^2 - \frac{3x}{2} = \frac{9}{2} [/latex]
[latex] \frac{x^2}{2} - \frac{3x}{2} + \frac{9}{16} = \frac{81}{16} [/latex]
[latex](x - \frac{3}{4} )^2 = \frac{81}{16} [/latex]
[latex]x - \frac{3}{4} = \frac{9}{4} ; x - \frac{3}{4} = - \frac{9}{4} [/latex]
[latex]x1 = 3 ; x2 = -1,5[/latex]
Решение смотри ниже на фото
Не нашли ответ?
Похожие вопросы